Determination Compensation, Leadership, And Organizational Culture on Performance Through Employee Work Satisfaction - Yasa , I Wayan Catra; Wibisono , Chablullah; Gulo , Eliaki; Prasetyo, Ary (International Journal of Psychosocial Rehabilitation, 2020)
The problem in this research, what is latent exogenous construction: compensation, leadership, organizational culture determines directly on the endogenous latent constructs: job satisfaction and employee performance at PT. VMI. This research aims to test and to analyze the direct determination of exogenous latent constructs: compensation, leadership, organizational culture towards endogenous latent constructs: job satisfaction and employee performance. The sampling technique uses simple random sampling techniques and research instruments using questionnaires of the total population of 702 employees of PT. 150 employees took VMI as a sample. Validity testing uses the Pearson Product Moment and reliability using Cronbach Alpha, which is processed with SPSS software. While the confirmatory factor analysis (CFA) test, the Normality Test and the test model used a Structural Equation Model (SEM) with Amos software. The results of this study are: Determination compensation has positive and significant direct to job satisfaction, but Determination compensation has negative not significant direct to the performance of employees. The determination of leadership has positive and significant direct to job satisfaction. The determination of leadership also has positive and significant direct to the performance of employees. Determination of organizational culture has positive not significant direct to job satisfaction. Determination of organizational culture has positive not significant directly to the employees’ performance. Determination Job satisfaction has positive and significant direct to employee performance.